2021
DOI: 10.2147/idr.s291199
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Preventative Practices (KAPs) Towards COVID-19 Among International Students in China

Abstract: The study aimed to find out about the knowledge, attitudes, and preventative practices of COVID-19 among international students in China during the pandemic. Material and Methods: A cross-section survey was conducted among 300 international students from 13 different universities in Hubei province of China between March and April 2020 which relied upon convenience sampling method. Results: Out of 300 respondents, 153 (51%) of the respondents were female students, of which the majority were single, undergraduat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…Thus, the majority of them have been able to find all adequate necessary information by using all available online social media and other platforms which are the current trend way of communication especially to the youth who are in majority as revealed in the study. The adequate and relevance of information dissemination has also been contributed by Chinese universities as they have contributed for the frequent provision of school notifications to the students during the pandemic time [31]. Our findings of this study on high dissemination means information agrees with other recent studies on IS in China which are said to have even gone to the extent of even helping in psychological perspectives to the students [35].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the majority of them have been able to find all adequate necessary information by using all available online social media and other platforms which are the current trend way of communication especially to the youth who are in majority as revealed in the study. The adequate and relevance of information dissemination has also been contributed by Chinese universities as they have contributed for the frequent provision of school notifications to the students during the pandemic time [31]. Our findings of this study on high dissemination means information agrees with other recent studies on IS in China which are said to have even gone to the extent of even helping in psychological perspectives to the students [35].…”
Section: Discussionsupporting
confidence: 86%
“…This study used exploratory methodology which relied both on reviewing the literature online on the official Chinese Government website, peer reviewed published articles and published Chinese school notifications. Furthermore, the study is part of the main study that was conducted to find Knowledge, Attitude and Preventative practices among international students in China that used a cross sectional design survey which was conducted on the first week of May 2020 in 13 selected universities in Hubei province of China [31] (See Fig. 2 Hubei province is located in central China and is one of the provinces that has many academic institutions in China with many international students close to 21,371 [10].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…According to the KAP model, knowledge, attitudes, and practice are inter-related [9,10], and previous studies have found that knowledge is the most crucial factor in preventive behavior regarding novel influenza A [22]. However, the result of the final hierarchical regression analysis in this study found that participants' attitudes, but not their knowledge about COVID-19, affected their preventative practice, although they also showed significant positive relationships [23][24][25].…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, it is difficult for most international students living in Daegu and Gyeongbuk to keep track of the continually changing guidelines announced by Korea's government or to find relevant information. Mostly, many international students often obtain COVID-19 related information through social media [9], so they need to be managed to avoid exposure to misinformation, particularly during the COVID-19 pandemic. Most of them are non-English speakers and may have difficulty understanding the official announcements provided in Korean and English.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research provides evidence that the level of KAP possessed by inhabitants dictates the success of the adopted measures [ 15 , 18 , 24 , 25 , 26 ]. Recently, there are some studies investigated KAP towards COVID-19 in different group, such as general residents [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], healthcare workers [ 24 , 37 , 38 , 39 , 40 , 41 ], students [ 9 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], patients [ 49 ], hospital visitors [ 50 ] and slums [ 51 , 52 ], during the COVID-19 pandemic. Most of KAP studies regarding COVID-19 discuss the group of general residents.…”
Section: Introductionmentioning
confidence: 99%